Effects of persistent organic pollutants (POPs) on soil microorganisms - Černohlávková, Jitka (2007)
Soil microorganisms play a key role in transformation and decomposition of organic matter in soil and are also significant part of food, nutrient and energy cycles in terrestrial ecosystems. Persistent organic pollutants (POPs) represent toxic and bioaccumulative chemicals that are wide spread and have a potential to remain in the environment unchanged for many years. Soil is in most cases a target dump of these substances and also the main source of secondary contamination. Therefore the risk potential for the non-target soil organisms (microorganisms) and main microbial processes should be assessed. This work summarized available information about toxic effects of POPs on soil microbial community as well as the application of microorganisms for POPs biodegradation. Practical part was focused on testing the effects of the persistent organochlorine pesticide, toxaphene, and industrial products, short-chain chlorinated paraffins, on soil microorganisms in laboratory incubation tests.